Smart City: a prospective study of patent-based technology - Silva, Vanessa de Souza (2020)
A smart city is a well-defined geographical area where technologies cooperate to create benefits for citizens, this way patent protection of these technologies is of great relevance. Within this context this research aims to carry out an analysis of patents in the area of ​​Smart Cities around the world, to reach this goal the Espacent database was used. The prospection was around the data from the main applicant countries and the international classification codes that most define the patents applied. The research found 412 results for published patents on the subject, most in the sections of physics and electricity. Since the precursor patent published in 2010 there has been an exponential increase in intellectual property publications, with China being the most dominant country for patents involving this subject, a fact that can possibly be corroborated due to the great investment of the country in technological innovations.